Depth, Significance, and Absence: Age-Effects in New British Theatre - Moore, Bridie (Age, Culture, Humanities: An Interdisciplinary Journal, 2014)
In view of Judith Butler’s assertion that identity as an effect is generated by “cultural apparatus” (Gender Trouble 199), this article interrogates the age-ef- fects generated by early twenty-first century mainstream British theatre. To ana- lyze the complex ways in which age is played out on the British stage—which seem at once both to challenge and to reiterate long-standing assumptions about age—it examines five productions seen in the autumn/winter season of 2011/12. It considers to what extent these productions disrupt the generation of normative age-effects and explores the often contradictory consideration of age in the “multiple realities of performance” (Lipscomb “The Play’s the Thing” 117). This exploration enlists the theories of Butler and others, including Anne Basting, who proposes a model of performance that enacts the body in its “temporal depth” (Stages of Age 22); Anca Cristofovici, who offers a conceptu- alization of the aged body as “significant form” (“Touching Surfaces” 275); and Kathleen Woodward, who ponders the psychic crisis resulting from a rejected, and therefore absent, reflection of the aging body (Aging and its Discontents 53–71). Viewing the staging of age through the lenses of “depth,” “signifi- cance,” and “absence” exposes the meanings of specific age performances and uncovers the age-effects of a theatre responding to the changing context of an aging Britain.